2021
DOI: 10.48550/arxiv.2105.13122
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Do the periodic activities of repeating fast radio bursts represent the spins of neutron stars?

Kun Xu,
Qiao-Chu Li,
Yuan-Pei Yang
et al.

Abstract: Fast radio bursts (FRBs) are mysterious radio transients with millisecond durations. Recently, a periodic activity of ∼16 day and a possible periodicity of ∼159 day were detected to arise from FRB 180916.J0158+65 and FRB 121102, respectively, and the spin period of a slow-rotation magnetar was further considered to be one of possibilities to explain the periodic activities of repeating FRBs. For isolated neutron stars, the spin evolution suggests that it's difficult to reach several hours. In this work, we mai… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 81 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…Also, possible periodic activities of soft gamma-ray repeaters of SGR 1806-20 and SGR 1935+2154 were found to be about 398.2 days (Zhang et al 2021) and 237 days (Zou et al 2021), respectively. Several scenarios have been proposed to ex-plain the periodic activities of FRBs (see Zhang 2020a): first, the FRB source is in a binary system with the observed period corresponding to the orbital period of this binary system (Dai et al 2016;Smallwood et al 2019;Ioka & Zhang 2020;Lyutikov et al 2020;Dai & Zhong 2020;Gu et al 2020;Mottez et al 2020;Decoene et al 2021;Kuerban et al 2021;Deng et al 2021;Wada et al 2021); second, the FRB is generated by the NS magnetosphere, and the observed periodic activities are due to the precession of the emitting region (Levin et al 2020;Yang & Zou 2020;Zanazzi & Lai 2020;Tong et al 2020;Li & Zanazzi 2021;Sridhar et al 2021); third, the observed period is due to the rotation of a very slow NS (Beniamini et al 2020;Xu et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Also, possible periodic activities of soft gamma-ray repeaters of SGR 1806-20 and SGR 1935+2154 were found to be about 398.2 days (Zhang et al 2021) and 237 days (Zou et al 2021), respectively. Several scenarios have been proposed to ex-plain the periodic activities of FRBs (see Zhang 2020a): first, the FRB source is in a binary system with the observed period corresponding to the orbital period of this binary system (Dai et al 2016;Smallwood et al 2019;Ioka & Zhang 2020;Lyutikov et al 2020;Dai & Zhong 2020;Gu et al 2020;Mottez et al 2020;Decoene et al 2021;Kuerban et al 2021;Deng et al 2021;Wada et al 2021); second, the FRB is generated by the NS magnetosphere, and the observed periodic activities are due to the precession of the emitting region (Levin et al 2020;Yang & Zou 2020;Zanazzi & Lai 2020;Tong et al 2020;Li & Zanazzi 2021;Sridhar et al 2021); third, the observed period is due to the rotation of a very slow NS (Beniamini et al 2020;Xu et al 2021).…”
Section: Introductionmentioning
confidence: 99%